STUDI ETNOFARMASI PENGGUNAAN TUMBUHAN OBAT BERKHASIAT PENYEMBUH LUKA DI SUKU BADUY, LEBAK, BANTEN. - Susanti, Kharisma Dewi Fadia; Peranginangin, Jason Merari; Boedirahardja, Partana (Jurnal Farmasi & Sains Indonesia, 2024)
Indonesian people use a lot of traditional medicinal plants as wound healers, one of them is the Baduy tribe. The use of medicinal plants in the Baduy tribe has not been well invented. This research aims to find out about the nutritious plants, how to soften and the use of plants as wound healers in the Baduy tribe.The research uses qualitative, quantitative methods and snowball sampling techniques with open-ended interviews to obtain data on medicinal plants that are useful as wound healers. The data obtained was processed using bioprospective analysis to find UV and ICF values. The most commonly used plants are rumput jariji, mata ayam, jarak jintir, pakis merak, and pacing tawar. The most common types of wounds suffered by the Baduy tribe were scratch wounds, dry wounds or scratches, bone fractures, scorpion bites, insect bite wounds. Methods of grinding and use on some plants by stopping, smoothing, peeling, diolizing or gluing directly to the skin. The highest Use Value value is rumput jariji with a number 1 as wound healing and the highest or most frequently experienced Informant concensus factor value by the Baduy tribe obtained a number of 0.66 which is wound from sharp objects.